2017
DOI: 10.1002/term.2577
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hepatocyte migration towards an endothelial cell tube network

Abstract: A crucial part of the engineering liver tissue is contribution of nonparenchymal cells and maintenance of a complex three-dimensional (3D) structure in vitro for their normal physiology and function. We generated 3D hepatic tissue using primary isolated rat hepatocytes and an endothelial cell tube network from human endothelial vein epithelial cells (HUVECs). To create the 3D hepatic tissue, coculture of primary hepatocytes and tube-structured HUVECs was performed on a Matrigel®. After the HUVECs formed the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It has been reported in several studies that the co‐culture model of endothelial cells and the other cells associated with diseases can simulate the phenotypic and morphological characteristics in vivo. Baimakhanov et al 31 observed that primary hepatocytes migrated spontaneously to the HUVEC tube network, and they hypothesized that this co‐culture model duplicated part of their normal physiology. In this study, HUVEC was used to simulate uterine spiral artery endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in several studies that the co‐culture model of endothelial cells and the other cells associated with diseases can simulate the phenotypic and morphological characteristics in vivo. Baimakhanov et al 31 observed that primary hepatocytes migrated spontaneously to the HUVEC tube network, and they hypothesized that this co‐culture model duplicated part of their normal physiology. In this study, HUVEC was used to simulate uterine spiral artery endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hepatocytes contributed to the process of liver fibrosis through changing migratory behavior and biological functions. Hepatocytes can undergo epithelial-mesenchymal phenotypic transition, which increase the migratory ability and changes in the mechanical properties of hepatocytes can regulate cell migration and mechanical signal transduction [ 14 , 15 , 16 ]. However, at present, whether matrix stiffness, a factor that significantly changes in the process of liver fibrosis, can regulate hepatocytes participate in the process of liver fibrosis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies utilize DMEM for the culture of thyroid cell lines [17]. While HDM was originally designed for the culture of hepatocytes, it has also been reported to be suitable for the culture of epithelial cells and certain kinds of gland cells, such as hepatic epithelial cells [15], salivary epithelial cells [18] and primary human lacrimal gland cells [19]. Similarly, thyroid cells, which are follicle epithelial cells isolated from the thyroid gland, may also be well-cultured and easily proliferate in epithelial cell culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Because no chemical treatments are needed in order to harvest the cell sheets with extracellular matrix, the native cellular function is maintained [4,6,15]. Furthermore, cell sheets have been shown to be able to be handled easily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation